Le dispositif d’analyse de situations professionnelles GPS et sa plateforme numérique - Paul Lehner; Jean-François Nordmann (Distances et Médiations des Savoirs, 2021)
Two aims guide this article. The first is to present the theoretical, methodological and practical choices underlying the design of the two components - face-to-face and distance learning - of the professional situation analysis device “GPS” (“Gérer Professionnellement les Situations”). The second is to discuss the perspective that this device, although initially designed and supported by Inspé teachers-researchers, is able to contribute to the school teachers’ professional autonomy thought as a collective emancipation from institutional power. The hypothesis is that, through the articulation of its two components added to its specific entry angle through the teachers’ uncertainty situations, the GPS device allows the collaborative development of new and non-prescribed knowledge about the complexity of professional situations and correlative teachers’ positioning, as well as the constitution of a new professionnel ethos based on the commitment to publicly share the analyses and call for their enrichment by the contribution of complementary points of view provided by other teachers and education actors. It is the interplay of these various dimensions that would allow the device to contribute to increasing the teachers’ power of action and professionalization and provide also a response to the discomforts of the profession and more specifically to the “ghost of powerlessness” and the recognition deficits.